Studi Perbandingan Kinerja Bohlam LED DC dan Bohlam LED AC untuk Pencahayaan Sistem PV Off-grid - Rinaldi, Reza Satria; Anggraini, Ika Novia; Herawati, Afriyastuti; Ladio, Wahyu Apriali (SURYA TEKNIKA, 2026)
The use of DC distribution is considered more efficient than AC in off-grid PV systems because it reduces energy conversion losses, especially in loads such as LED lights. A comparative study of DC and AC LED lighting is needed to improve the efficiency of offgrid PV systems. This study compares the performance of DC and AC LED bulbs for lighting a 12 V off-grid PV system. Testing on a 12 V off-grid PV system was carried out by collecting data in the form of DC power from a 12 V VRLA battery and light intensity (lux) produced by samples of DC and AC LED bulbs with nominal power of 10 W, 20 W, and 30 W, with uniform technical specifications. The results of the study indicate that DC LED bulbs are more efficient than AC LED bulbs both in power consumption from off-grid PV systems and in producing light. Thus, lighting in a 12 V off-grid PV system is more efficient using DC LED bulbs.